Analysis of Pawongan Values as Characters That Nurture Good Human Relationships in Roald Dahl’s The Witches - Suciarti, Ni Ketut; Suwastini, Ni Komang Arie; Mahayanti, Ni; Minxia, Zhu; Mahardika, I Gusti Ngurah Agung Wijaya (Universitas Airlangga, 2025)
This article explores the representation of Tri Hita Karana values in Roald Dahl’s The Witches. By focusing on the Pawongan values as the framework for building good relationships with other people, the present study follows the interactive qualitative data analysis from Miles, Huberman, and Saldana in conducting the simultaneous process of the data classification, data display, and conclusion drawing immediately after data collection to ensure trustworthy results. The analysis revealed that the novel includes curiosity, courage, intelligence, loving, and responsibility as the values that could build good relationships with other people, as guided by the Pawongan values in the Tri Hita Karana local wisdom. These findings imply that although Roald Dahl's novel The Witches is written in English by a British author and set in England and Norway, the novel poses a strong relevance for readers with a Balinese background, opening an opportunity to introduce local wisdom through world literature.